POLA KONSUMSI NON MAKANAN RUMAH TANGGA MISKIN DI KABUPATEN ACEH BARAT - Yayuk Eko Wahyuningsih; Mahrizal Mahrizal; Masykur Masykur (Universitas Teuku Umar, 2018)
This research aimed to analyze the variables that affect the consumption patterns of impoverished households exspecially for non-food items. The data used were primary data in the form of a questionnaire and secondary data from the BPS and Regional Development Planning Agency. The data collection method was clustered two-stage sampling that was followed by random sampling. The model for this research was multiple linear regression analysis using a dummy variable with these equation models for non-food consumption patternCNM = o + 1YK + 2EK + 3AK + 4PK + 5UK + c1D1 +The research results showed that the R value for the non-food consumption pattern, the R value was 0.9415, which meant that there was a very strong relationship between the free variables and the bound variable by 94.15 percent; the R2 adj value for the non-food consumption pattern was 0.8816 which meant that the variation in the non-food consumption pattern could be explained as much as 88.16 percent by the variables. These variables covered household income (YK), economic activities of the head of family (EK), number of family members (AK), level of education of the head of family (PK), and age of the head of family (UK) as well as the dummy variable. The remaining 11.84 percent was explained by other variables outside this research model.The equation for the non-food consumption pattern of impoverished households is CNM = - 60,062+0.21515YK+ 508.02EK+ 3,939.2AK+2,815PK+314.14UK+9,351DBased on these findings, the researcher recommends that the regency government take strategic steps to address poverty through identifying absolutely impoverished and relatively impoverished households, expanding employment, increasing entrepreneurship culture, and adding or improving transportation-related infrastructure. In addition, it is necessary that NGOs and higher education institutions in this regency provide public assistance or services.Keywords: income, spending, impoverished households